Effect of Spraying Salicylic Acid and Collection Dates of Corn Silk (Zea mays L.) on Growth, Yield and Content of Some Antioxidant Compounds - Maher H.S. Al-Mohammad (Journal of Global Pharma Technology, 2017)
A filed experiment was conducted during the autumn season of 2016 to study the effect of foliar application salicylic acid (SA) at concentrations 0, 50, 100 and 200 mg.L-1 and collection dates (CD) at 14, 28 and 32 days after flowering and their interactions on growth parameters (plant length, total leaves number, leaf area and total chlorophyll), yield (Fresh and dry weight, plant yield and dry productivity) and some antioxidant compounds(total phenol compounds, flavonoids, anthocyanins, carotene, ascorbic acid and glutathione) of corn silk (Zea mays L.). Results of analysis of variance showed that SA affect were given increased   significantly impact (P<0.05)  when increased concentrations on all growth parameters of plant and yield, while late CD were increased leaf area, plant yield and dry productivity of corn silk, but the early CD decreased total chlorophyll and fresh weight of corn silk. The interaction between SA 200 mg.L-1×CD 14 days were given high amount of total phenol compounds, carotene, ascorbic acid and glutathione (140.53, 8.96 mg.Kg-1 DW, 115.34 and 16.71 mg.Kg-1 FW) respectively, and treat of SA 200 mg.L-1×CD 32 days were given high amount of total flavonoids and anthocyanin (48.57 and 5.93 mg.Kg-1 DW).  Keywords: Corn silk, Salicylic acids, Collection dates, Antioxidant compounds.